David Glick Award Lecture | SUPER RESOLUTION MICROSCOPY: NEW APPROACHES TO DISCOVER THE TOPOGRAPHICAL SECRETS OF GENE REGULATION (European Journal of Histochemistry)
The spatio-temporal folding pattern of the nuclear chromatin has emerged as a decisive key parameter for transcriptional control and hence for gene regulation1. A wealth of information on this subject has been obtained from a variety of biochemical approaches2. These methods allowed to measure relative contact frequencies between specific DNA sequences; relative distances and thus relative chromatin domain sizes; or relative DNA densities. Based on such data, even the calculation of probable 3D structures has become possible. However, the real processes of transcription regulation do not take place in the space of probability, but in real space (nm) and in real time (s);therefore an understanding of these mechanisms is only possible through knowledge of the actual processes in real space and in real time, measured in absolute units: Hence, complementary information is required on absolute distances (nm), absolute positions (x,y,z), absolute sizes (μm3), absolute DNA densities (Mbp/μm3), and really existing, not only probable structures in space and time (x,y,z,t) at the single cell level. Such topographical information may now be obtained by a variety of super-resolution methods3,4, with perspectives down to the sub-nm resolution range5.